2012
DOI: 10.1590/s1413-86702012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Early HHV-6 replication is associated with morbidity non-related to CMV infection after kidney transplantation

Abstract: Herpesvirus 6, human DNA virus infections Clinical diagnosisPolymerase chain reaction A B S T R A C T Human herpesvirus type 6-(HHV-6) has been associated with morbidity after liver transplantation.Objective: The aim of this study was to determine the HHV-6 seroprevalence among donorrecipient pairs, analyze the incidence of early active infection, its clinical manifestation, interaction with CMV, and the related morbidity in the first year after kidney transplantation.Methods: 46 donor-recipient pairs had IgG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…It has been demonstrated that ganciclovir or valganciclovir prophylaxis decreases HHV‐6 viremia incidence in SOT recipients, which could explain the low prevalence of HHV‐6 in our study, when compared to others . The low frequency of HHV‐6 detection in this cohort made it difficult to observe its influence on acute rejection, although such association is not a consensus among different authors …”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…It has been demonstrated that ganciclovir or valganciclovir prophylaxis decreases HHV‐6 viremia incidence in SOT recipients, which could explain the low prevalence of HHV‐6 in our study, when compared to others . The low frequency of HHV‐6 detection in this cohort made it difficult to observe its influence on acute rejection, although such association is not a consensus among different authors …”
Section: Discussioncontrasting
confidence: 61%
“…One of the limitations of the study could be the short follow‐up period for long‐term outcomes, such as PTLD. The modest sample size (82 patients, 409 samples) of the study may have limited further analysis, even though it is similar or even larger than other publications on the subject . Furthermore, information on EBV and HCMV serological status of donors were not available making it impossible to classify risk groups as D+/R‐.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6 Some but not all studies have shown that HHV-6 is associated with outcomes including rejection, opportunistic infections, and mortality after transplantation. [6][7][8][9][10][11] However, these data are mainly based on studies that were conducted several decades ago, included small number of high-risk mostly D+R-patients (the subgroup at highest risk for poor outcomes), assessed short-term outcomes, and composed of patients who were receiving antiviral prophylaxis. 7,[12][13][14] The most important limitations of the previous studies pertain to methodologic issues, including use of suboptimal assays for the detection of viremia such as antibody responses and semi rather than sensitive quantitative molecular assays, and failure to distinguish high-grade HHV-6 replication from chromosomal integration.…”
Section: Introductionmentioning
confidence: 99%